ES piliečių, turinčių nuolatinio gyventojo statusą Jungtinėje Karalystėje, teisė gyventi kartu su šeimos nariais po „Brexit“ - Bučinskaitė, Monika; Nikartas, Deivydas (Vilnius University Open Series, 2020)
This paper analyses the impact of the United Kingdom withdrawal procedure on the rights of EU citizens with permanent residence status in the United Kingdom to live with their family members in the country after Brexit and the legal challenges and perspectives arising from this procedure. It provides an overview of the international and national regulatory frameworks for the free movement of persons, and analyses possible models of relations between the United Kingdom and the EU after Brexit in relation to this fundamental freedom. The research focuses on the rights of people working in the United Kingdom to live with their family members and provides prospects for future legal regulation once the United Kingdom is no longer a member of the EU.
Keywords: none